ANALISIS PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (Studi pada Badan Pengembangan Sumber Daya Manusia Daerah Provinsi Jawa Tengah) - Immanuel, Immanuel; Mas’ud, Fuad (Faculty of Economics and Business Diponegoro University, 2017)
Employee performance is an important element in the organization. Like most other organizations, Human Resources Development Agency employess of Central Java Province also faces problems regarding the performance of its employees. Organizational culture issues that have not been fully implemented well and also monotonous working environment conditions that can affect the work motivation that will affect the performance. This study aims to investigate the influence of organizational culture and work motivation to employee performance of Human Resources Development Agency employees of Central Java Province. This study uses two independent variables, namely organizational culture and work motivation, as well as the dependent variable of employee performance. The sample in this research is 94 employees of Human Resources Develompent Agency employees of Central Java Province determined by using census method. Based in multiple linier regression analysis, the result of this study indicate the variables of organizational culture and work motivation have a positive effect on employee performance. Adjusted r square value indicating that the independent variable can explain the dependent variabel of 37,9 % ,while the remaining is influenced by other variables not used in this study.